Method for producing recycled positive electrode active material
By mixing a positive electrode composite material with an alkali metal compound below the activation treatment agent's melting point and subsequent controlled heating, the method improves the charge/discharge characteristics of recycled cathode active materials, matching those of unused materials.
Patent Information
- Application Number
- JP2024054348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2044-03-28
AI Technical Summary
Existing methods for recycling cathode active materials from waste batteries struggle to maintain the charge/discharge characteristics comparable to those of batteries using unused materials, particularly due to the deterioration of positive electrode active materials during the recycling process.
A method involving mixing a positive electrode composite material with an activation treatment agent containing alkali metal compounds, heating the mixture below the melting start temperature of the agent, and then recovering the positive electrode active material, followed by a higher temperature heating to enhance crystallite size, thereby improving charge/discharge characteristics.
The method enables the production of recycled positive electrode active materials with charge/discharge characteristics comparable to those of unused materials, enhancing the performance of batteries manufactured using these recycled components.
Smart Images

Figure 0007620142000001 
Figure 0007620142000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]
[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.
[0003] For example, Patent Document 1 discloses a method of recovering a positive electrode active material by mixing a positive electrode composite with an activation treatment agent containing an alkali metal compound, heating the mixture to a holding temperature equal to or higher than the melting temperature of the activation treatment agent, and removing decomposition products and the activation treatment agent with water or the like. This method is cost-effective in that it does not use an organic solvent and directly recovers a positive electrode active material from battery waste. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]
[0005] The positive electrode mixture includes a positive electrode mixture in a positive electrode recovered from a discarded battery and a positive electrode mixture in a positive electrode waste generated during the manufacturing process of a positive electrode or a battery. In recent years, not only recycling of a positive electrode active material from a positive electrode mixture in a positive electrode recovered from a discarded battery, but also recycling of a positive electrode active material from a positive electrode mixture in a positive electrode waste generated during the manufacturing process of a positive electrode or a battery has been considered.
[0006] Therefore, an object of the present invention is to provide a method for producing a recycled positive electrode active material that can make the charge / discharge characteristics of a battery produced using a recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material. [Means for solving the problem]
[0007] The present invention includes, for example, the following [1] to [5]. [1] A method for producing a recycled positive electrode active material, comprising the following steps: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture to a temperature lower than the melting start temperature of the activation treatment agent to obtain a heated mixture. (3) recovering the heated positive electrode active material from the heated mixture; [2] The method according to [1], wherein in the step (3), the mixture after heating is heated at a temperature higher than that in the step (2), and the heated positive electrode active material is recovered. [3] The method according to [1] or [2], wherein the positive electrode active material contains a lithium compound. [4] The method according to any one of [1] to [3], wherein the positive electrode active material contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg [5] The method according to any one of [1] to [4], wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Effect of the Invention
[0008] According to the present invention, it is possible to provide a method for producing a recycled positive electrode active material that can make the charge / discharge characteristics of a battery produced using a recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Method of manufacturing recycled positive electrode active material) A method for producing a recycled positive electrode active material will be described below.
[0010] A method for producing a recycled positive electrode active material according to one embodiment of the present invention includes the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to a temperature lower than the melting start temperature of the activation treatment agent to obtain a heated mixture. Step (3): A step of recovering the heated positive electrode active material from the heated mixture.
[0011] In one embodiment of the method for producing a recycled positive electrode active material, when a mixture of a positive electrode composite and an activation treatment agent is heated, the mixture is heated to a temperature below the melting start temperature of the activation treatment agent, and then the heated positive electrode active material is recovered from the heated mixture. The inventors have found that it is possible to produce a recycled positive electrode active material without heating the mixture to a temperature equal to or higher than the melting start temperature of the activation treatment agent as in the past, and that the charge / discharge characteristics of a battery produced using the recycled positive electrode active material can be made more comparable to those of a battery produced using an unused positive electrode active material than in the past. The inventors speculate that the reason for this is as follows.
[0012] That is, the positive electrode mixture in the waste of the positive electrode generated in the process of manufacturing the positive electrode or the battery (for example, the end of the positive electrode, the positive electrode of a non-standard product) is hardly deteriorated. In addition, even if the positive electrode mixture in the positive electrode recovered from the discarded battery is relatively deteriorated, there is a relatively small degree of deterioration. Therefore, when mixing these relatively deteriorated positive electrode mixtures with an activation treatment agent and heating the resulting mixture, it is possible to sufficiently activate the positive electrode active material even at a low heating temperature, and since the heating temperature is low, the elution of the metal in the positive electrode active material into the molten salt reaction field of the activation treatment agent is suppressed, so that the charge and discharge characteristics can be achieved to the same extent as the charge and discharge characteristics of a battery manufactured using an unused positive electrode active material. In addition, after heating the mixture of the positive electrode mixture and the activation treatment agent, the mixture is heated at a temperature higher than that in the process of heating the mixture of the positive electrode mixture and the activation treatment agent, and the crystallite size is sufficiently increased, thereby improving the charge and discharge characteristics. For these reasons, according to the present invention, the charge / discharge characteristics of a battery produced using a recycled positive electrode active material can be made more comparable to those of a battery produced using an unused positive electrode active material. However, the mechanism of the present invention is not limited to the above.
[0013] Each step will be described in detail below.
[0014] Pre-process (A): Positive electrode composite preparation process First, a positive electrode mixture containing a positive electrode active material is prepared.
[0015] [Cathode active material] Examples of the positive electrode active material include composite compounds containing one or more of the following elements as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten.
[0016] The positive electrode active material may be composed of only a single compound, or may be composed of a plurality of compounds.
[0017] The positive electrode active material preferably contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
[0018] The positive electrode active material preferably contains a compound represented by the following formula (A).
[0019] Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements excluding Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metal elements excluding O and P, -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5 are satisfied.
[0020] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X include F, S, Cl, Br, I, Se, Te, N, etc.
[0021] The positive electrode active material preferably contains a composite oxide containing at least Li and Ni.
[0022] In the positive electrode active material, M 1 The molar fraction of Ni in the above range is preferably 0.3 to 0.95.
[0023] The crystal structure of the positive electrode active material (for example, composite oxide) is not particularly limited, but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is more preferred.
[0024] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0025] The monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0026] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m contained in a hexagonal crystal structure, or the space group C2 / m contained in a monoclinic crystal structure.
[0027] The crystal structure of the positive electrode active material can be identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.
[0028] The particle size of the positive electrode active material in the positive electrode mixture is not particularly limited, but may be about 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments). A volume-based cumulative particle size distribution curve is created from the particle size distribution, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material.
[0029] There is no particular limitation on the content of the positive electrode active material in the positive electrode mixture.
[0030] [Binding agent] The positive electrode mixture may contain a binder. In the case where the positive electrode mixture contains a binder, the particles of the positive electrode active material may be bound to each other by the binder.
[0031] Examples of the binder (binder before activation treatment) contained in the positive electrode mixture include thermoplastic resins, and specific examples thereof include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). The binder may be used alone or in combination of two or more kinds.
[0032] The content of the binder in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.
[0033] [Conductive material] The positive electrode mixture may contain a conductive material and / or an electrolyte. When the positive electrode mixture contains a binder and a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by the binder. The positive electrode mixture may contain a fluorine compound derived from the binder and / or the electrolytic solution (e.g., the electrolyte in the electrolytic solution).
[0034] Examples of the conductive material include metal-based conductive materials such as metal particles; and carbon-based conductive materials made of carbon materials.
[0035] Specific examples of carbon-based conductive materials include graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers and carbon nanotubes).
[0036] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.
[0037] The specific surface area of the carbon material used as the carbon-based conductive material is 0.1 to 500 m 2 In this case, the conductive material may have a specific surface area of 30 m 2 / g or more, and is made of only carbon-based conductive materials with a specific surface area of 30 m 2 / g or more, and may be carbon black having a specific surface area of 30 m 2 When an activating treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the rate of oxidation treatment of the carbon-based conductive material can be increased, and even a carbon material having a small specific surface area can be oxidized in some cases.
[0038] The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.
[0039] [Electrolytes and Solvents] The electrolyte is a component derived from the electrolyte of the battery and impregnated into the positive electrode mixture. Examples of the electrolyte include LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, LiCF3SO3, etc. The content of the electrolyte contained in the positive electrode mixture is not particularly limited, but may be 0.0005 to 7 mass%.
[0040] The positive electrode mixture may contain a solvent derived from the electrolyte, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.
[0041] [Recovery of cathode mixture] The positive electrode mixture can be obtained by separating and recovering the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer.
[0042] The "scrap positive electrodes" may be positive electrodes recovered from discarded batteries, and waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. The discarded batteries may be used batteries, or unused but non-standard batteries. The waste positive electrodes may be the ends of positive electrodes generated during the manufacturing process of batteries, or non-standard positive electrodes. As the positive electrode composite, waste positive electrode composite not attached to a current collector (waste generated during the manufacturing process of the positive electrode composite) may also be used.
[0043] The waste positive electrode has a current collector which is a metal foil such as aluminum foil or copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.
[0044] Examples of a method for separating the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer include a method for mechanically peeling the positive electrode mixture layer from the current collector (e.g., a method for scraping the positive electrode mixture layer from the current collector), a method for penetrating a solvent into the interface between the current collector and the positive electrode mixture layer to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.
[0045] Previous process (B): Positive electrode mixture cleaning process Next, when the positive electrode mixture contains an electrolyte, it is preferable to bring the prepared positive electrode mixture into contact with an electrolyte washing solvent to remove at least a part of the electrolyte from the positive electrode mixture. Specifically, the positive electrode mixture containing the positive electrode active material and the electrolyte is brought into contact with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.
[0046] Solid-liquid separation is an operation for separating a slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.
[0047] The electrolyte cleaning solvent is not particularly limited. Examples of the electrolyte cleaning solvent include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.
[0048] The positive electrode mixture can be brought into contact with the electrolyte washing solvent in a known contact device for powder and liquid (for example, a stirring tank).
[0049] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, it is preferable to obtain a slurry by stirring the positive electrode mixture and the electrolyte washing solvent. The peripheral speed of the tip of the stirring blade may be 0.1 to 1.0 m / s.
[0050] In the washing step of the positive electrode composite material, after solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is again brought into contact with the electrolyte washing solvent to obtain a slurry, and the slurry is again separated into a solid component and a liquid component. In the washing step of the positive electrode composite material, rinsing may be performed multiple times. The slurry concentration in the rinsing can be adjusted as desired. In the rinsing, the slurry can also be stirred as described above.
[0051] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material may change from a layered rock salt structure to a spinel structure. LiPF6+16LiMO2+2O2→ 6LiF+Li3PO4+8LiM2O4
[0052] Furthermore, when the activation treatment agent contains lithium carbonate, lithium may be consumed through the following reaction. LiPF6+4Li2CO3→ 6LiF+Li3PO4+4CO2
[0053] The separated solid component may be dried, if necessary, by reducing pressure and / or heating to remove the electrolyte washing solvent. The heating temperature may be 50 to 200°C.
[0054] Step (1): Activation treatment agent mixing step Next, the prepared positive electrode mixture and an activation treatment agent containing one or more types of alkaline compounds are mixed to obtain a mixture.
[0055] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods. The order in which the positive electrode mixture and the activation treatment agent are mixed is not particularly limited.
[0056] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.
[0057] As a mixing method, dry mixing is preferred because mixing can be performed more easily. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.
[0058] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Corporation).
[0059] The activation treatment agent used in this step will be described in detail below.
[0060] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. The activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Here, potassium and / or sodium may be referred to as alkali metal element X. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or sodium compound.
[0061] When the activation treatment agent comes into contact with the positive electrode active material, the positive electrode active material can be activated. In particular, when the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the positive electrode active material is improved, and the activation of the positive electrode active material is further promoted.
[0062] In addition, the positive electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the positive electrode active material.
[0063] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target positive electrode active material, etc., and is usually 50 mass% or more, preferably 70 mass% or more, relative to the total mass of the activation treatment agent, and may be 100 mass% (an embodiment in which the activation treatment agent is essentially composed of alkali metal compounds).
[0064] The concentration of at least one alkali metal selected from the group consisting of potassium and sodium in the alkali metals contained in the alkali metal compound can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.
[0065] Examples of alkali metal compounds that are components of the activation treatment agent include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates, etc. These can be used alone or in combination as components of the activation treatment agent.
[0066] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0067] Here, in order to further enhance the activation effect of the positive electrode active material, the activation treatment agent may contain, in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds, the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.
[0068] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, the activation treatment agent preferably contains a lithium compound in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds. Suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.
[0069] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.
[0070] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and can be less than 50 mass% relative to the total mass of the activation treatment agent.
[0071] The amount of the activation treatment agent added in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the mass of the positive electrode active material contained in the positive electrode mixture.
[0072] When the activation treatment agent contains a potassium compound and a lithium compound, the ratio of the lithium content (molar) to the potassium content (molar) (lithium content / potassium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0073] When the activation treatment agent contains a sodium compound and a lithium compound, the ratio of the lithium content (molar basis) to the sodium content (molar basis) (lithium content / sodium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0074] When the activation treatment agent contains a potassium compound, the potassium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.
[0075] When the activation treatment agent contains a sodium compound, the sodium content (molar) contained in the activation treatment agent may be 1 to 200%, 10 to 200%, 50 to 200%, or 100 to 200%, 1% or more and less than 150%, 10% or more and less than 150%, 50% or more and less than 150%, or 100% or more and less than 150%, relative to the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0076] The number of moles of the alkali metal compound in the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent can be added so that the number of moles of the alkali metal element is 0.001 to 200 times the number of moles of the positive electrode active material (e.g., Formula A) contained in the positive electrode composite.
[0077] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material from the positive electrode mixture can be reduced, the oxidative decomposition rate of the carbon-based conductive material and the binder can be increased, the effect of preventing the generation of corrosive gas in the heating step can be improved, and the discharge capacity of the battery manufactured using the obtained positive electrode active material can be further increased.
[0078] At least one of the alkali metal compounds contained in the activation treatment agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."
[0079] By using an alkaline activation treatment agent, the generation of corrosive gas during the heating process can be further suppressed, so that the discharge capacity of the battery manufactured using the recovered positive electrode active material can be further increased. In addition, by using an alkaline activation treatment agent, the treatment speed of the carbon-based conductive material and the binder can be increased.
[0080] Examples of the alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in the alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals. Specifically, hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, and CsCO3; hydrogen carbonates such as LiHCO3, NaHCO3, KHCO3, RbHCO3, and CsHCO3; oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; and superoxides such as LiO2, NaO2, KO2, RbO2, and CsO2. One or more of these may be contained in the activation treatment agent.
[0081] In addition, when the conductive material contained in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the heating step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."
[0082] Use of an activation treatment agent having such oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the obtained positive electrode active material, and can also improve the effect of preventing the generation of corrosive gases during the heating process.
[0083] Examples of alkali metal compounds having the oxidizing power required to oxidize carbonaceous conductive materials and hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.
[0084] Specific examples include superoxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; LiO2, NaO2, KO2, RbO2, and CsO2; nitrates such as LiNO3, NaNO3, KNO3, RbNO3, and CsNO3; sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, and Cs2SO4; vanadates such as LiVO3, NaVO3, KVO3, RbVO3, and CsVO3; and molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, and CsMoO4.
[0085] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.
[0086] The alkali metal compound may be a carbonate or sulfate, or at least one selected from the group consisting of Li2CO3, Na2SO4, Na2CO3, and K2CO3, from the viewpoint of making it easier to make the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material.
[0087] Process (2): Heating process The heating step is a step of heating the mixture obtained in step (1) (hereinafter sometimes referred to as the "mixture before heating") to a temperature below the melting start temperature of the activation treatment agent. The mixture obtained in this heating step is sometimes referred to as the "mixture after heating." In this specification, "heating to a temperature below the melting start temperature of the activation treatment agent" means heating while maintaining a temperature below the melting start temperature of the activation treatment agent (heating at a holding temperature below the melting start temperature of the activation treatment agent). In addition, "heating to a temperature below the melting start temperature of the activation treatment agent" means not heating at a temperature equal to or higher than the melting start temperature of the activation treatment agent.
[0088] The "melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase.
[0089] The melting start temperature (Tmp) of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, 5 mg of the mixture before heating is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting start temperature (Tmp).
[0090] The temperature to which the mixture before heating is heated may be 700° C. or lower, 650° C. or lower, 600° C. or lower, or 550° C. or lower, from the viewpoint of suppressing deterioration of the crystal structure of the positive electrode active material due to rapid generation of hydrogen fluoride, carbon dioxide, and water produced by decomposition of the binder, conductive material, and the like contained in the positive electrode mixture and contacting the positive electrode active material, and making it easier to achieve charge / discharge characteristics equivalent to those of a battery produced using unused positive electrode active material.
[0091] The temperature to which the mixture before heating is heated may be 150° C. or higher, 200° C. or higher, 250° C. or higher, 300° C. or higher, 350° C. or higher, 400° C. or higher, or 450° C. or higher, from the viewpoint of promoting decomposition of the binder, conductive material, etc., and making it easier to achieve charge / discharge characteristics comparable to those of a battery produced using an unused positive electrode active material.
[0092] The melting start temperature (Tmp) of the activation treatment agent is preferably 900° C. or less, more preferably 800° C. or less, further preferably 700° C. or less, and particularly preferably 600° C. or less. There is no lower limit to the melting start temperature (Tmp) of the activation treatment agent, but it may be, for example, 150° C.
[0093] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the positive electrode composite material and the activation treatment agent, the melting start temperature (Tmp) of the activation treatment agent becomes lower than the melting point of the activation treatment agent.
[0094] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10° C. / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting point of the activation treatment agent.
[0095] The atmosphere for heating is not particularly limited, and may be an oxygen-containing gas such as air, nitrogen, argon, carbon dioxide, or a mixture of these gases. The pressure of the atmosphere is not particularly limited, and may be atmospheric pressure, a reduced pressure atmosphere, or a pressurized atmosphere.
[0096] In the step (2), the mixture before heating is heated to a temperature lower than the melting initiation temperature (Tmp) of the activation treatment agent as described above, whereby the following effects occur.
[0097] By heating the mixture before heating to a temperature below the melting start temperature (Tmp) of the activation treatment agent, hydrogen fluoride and carbon dioxide produced by decomposition of the binder, conductive material, etc. contained in the positive electrode mixture are rapidly generated, and deterioration of the crystal structure of the positive electrode active material due to contact of these with the positive electrode active material is suppressed, making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material. In addition, a crystal structure repair effect can be obtained by heating the mixture before heating together with the activation treatment agent.
[0098] The heated activation treatment agent comes into contact with the carbon-based conductive material and the binder, thereby increasing the rate of oxidative decomposition of the conductive material and the binder, and the heated activation treatment agent comes into contact with the fluorine compounds derived from the binder, the electrolyte, etc., thereby stabilizing the fluorine components as alkali metal fluorides, preventing the generation of hydrogen fluoride, which is a corrosive gas, and further suppressing the deterioration of the crystal structure of the positive electrode active material.
[0099] Furthermore, when the activation treatment agent contains the same alkali metal as the positive electrode active material, it is also possible to supply the alkali metal that is insufficient for the positive electrode active material.
[0100] The temperature of the heating step and the holding time at that temperature can be appropriately adjusted depending on the types and combinations of the positive electrode active material, binder, conductive material, and alkali metal compound and other compounds contained in the activation treatment agent that constitute the positive electrode mixture. Usually, the temperature is in the range of 100 to 1000°C, and the holding time is about 10 minutes to 24 hours.
[0101] The temperature of the heating step is preferably lower than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each compound alone by mixing multiple types of compounds. When the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is the melting point of the alkali metal compound.
[0102] After the heating step, the mixture can be cooled to any temperature (for example, about room temperature) as necessary. In this way, a heated mixture containing a heated positive electrode active material is obtained.
[0103] Step (3): Positive electrode active material recovery step The positive electrode active material recovery step is a step of recovering the heated positive electrode active material from the heated mixture (or the solid component obtained in step (3a), the solid component obtained in step (3b), or the solid component obtained in step (3c)) after the heating step of step (2).
[0104] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (such as alkali metal compounds), undecomposed conductive material and binder, and other undecomposed materials of the positive electrode mixture. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte. In step (3), it is preferable to remove the components derived from the activation treatment agent (such as alkali metal compounds), the unreacted activation treatment agent, the undecomposed conductive material and binder, and other undecomposed materials of the positive electrode mixture, from the viewpoint of more easily achieving rate characteristics equivalent to those of a battery manufactured using an unused positive electrode active material by increasing the purity of the positive electrode active material.
[0105] Examples of methods for separating and recovering the heated positive electrode active material from the heated mixture include a solid-liquid separation method in which a solvent such as water is added to the mixture to form a slurry, followed by solid-liquid separation, and a vaporization separation method in which the mixture is heated to vaporize and separate components other than the heated positive electrode active material. The solid-liquid separation method will be described below.
[0106] Step (3a): Solid-liquid separation step Step (3a) is a step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component.
[0107] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (such as alkali metal compounds), and undecomposed materials of the positive electrode mixture such as undecomposed conductive material and binder, etc. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.
[0108] In order to separate and recover the heated positive electrode active material from the heated mixture, a liquid containing water (liquid) is added to the mixture to form a slurry, which is then subjected to solid-liquid separation to separate the solid component and the liquid component.
[0109] The liquid used in the slurrying step is not particularly limited as long as it contains water. The amount of water in the liquid may be 50% by mass or more. In order to increase the solubility of water-soluble components or to increase the processing speed, components other than water may be added to the liquid to adjust the pH.
[0110] Suitable examples of the liquid containing water include pure water and alkaline cleaning liquid. Examples of the alkaline cleaning liquid include an aqueous solution of at least one anhydride selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate, and a hydrate thereof. Ammonia can also be used as the alkali.
[0111] The resulting slurry contains a solid component mainly containing the positive electrode active material after heating and a liquid component containing water-soluble components other than the positive electrode active material. The liquid component contains an alkali metal component derived from the activation treatment agent and / or a fluorine component derived from the binder and the electrolyte.
[0112] The amount of liquid to be added to the mixture is appropriately determined taking into consideration the amounts of the post-heating positive electrode active material and water-soluble components other than the positive electrode active material contained in the mixture.
[0113] In step (3a), it is preferable to obtain a slurry by stirring the mixture after heating with a liquid containing water. This promotes dissolution of the water-soluble components. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.
[0114] The slurry formed in the slurrying step is then subjected to solid-liquid separation. Solid-liquid separation is a step of separating the slurry into a liquid component and a solid component. The method of solid-liquid separation may be a conventional method, such as filtration or centrifugation.
[0115] In step (3a), after the solid-liquid separation, the obtained solid component may be rinsed. Rinsing is an operation in which the obtained solid component is contacted again with a liquid containing water to obtain a slurry, and then the slurry is separated again into a solid component and a liquid component. In step (3a), rinsing may be performed multiple times. The slurry concentration in the rinse may be the same as above.
[0116] Process (3b): Drying process Step (3b) is, for example, a step of exposing the solid component obtained in step (3a) to a heating and / or reduced pressure environment to remove water from the solid component.
[0117] The heating temperature is preferably 100°C or higher to remove water. It is more preferably 150°C or higher to remove water sufficiently. In particular, a temperature of 250°C or higher is preferable because the discharge capacity of a battery manufactured using the obtained positive electrode active material is further increased. The temperature in the drying step may be constant, or may be changed stepwise or continuously. The heating temperature range may be, for example, 10°C or higher and less than 900°C.
[0118] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It can be Pa.
[0119] Process (3c): Annealing process Step (3c) is a step of heating the mixture after heating (or the solid component obtained in step (3a) or the solid component obtained in step (3b)) at a temperature higher than that in step (2).
[0120] The temperature to which the mixture after heating is heated may be greater than 700° C., 750° C. or higher, 800° C. or higher, 850° C. or higher, or 900° C. or higher, from the viewpoint of vaporizing components other than the positive electrode active material and removing impurities, and from the viewpoint of making the crystallite size of the positive electrode active material sufficiently large, thereby more easily achieving charge / discharge characteristics equivalent to those of a battery produced using an unused positive electrode active material.
[0121] The temperature to which the mixture after heating is heated may be equal to or higher than the melting temperature of the activation treatment agent, from the viewpoint of making it easier to achieve charge / discharge characteristics comparable to those of a battery manufactured using an unused positive electrode active material by sufficiently increasing the crystallite size of the positive electrode active material. In the annealing step, the mixture after heating may be heated at a temperature that is 20° C. or higher, 30° C. or higher, 40° C. or higher, 50° C. or higher, 100° C. or higher, 150° C. or higher, or 200° C. or higher than the melting temperature of the activation treatment agent.
[0122] The temperature to which the mixture after heating is heated may be 1500° C. or less, 1400° C. or less, 1300° C. or less, 1200° C. or less, 1000° C. or less, or 950° C. or less, from the viewpoint of suppressing thermal deterioration of the positive electrode active material and making it easier to achieve charge / discharge characteristics comparable to those of a battery produced using an unused positive electrode active material.
[0123] When the heating temperature in step (2) is T1 and the heating temperature in step (3) is T2, from the viewpoint of more easily achieving charge / discharge characteristics equivalent to those of a battery produced using an unused positive electrode active material, T2 / T1 may be 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, or 2 or more, and from the same viewpoint, it may be 2.5 or less, 2.4 or less, 2.3 or less, or 2.2 or less.
[0124] When the heating temperature in step (2) is T1 and the heating temperature in step (3) is T2, T2-T1 may be 250° C. or more, 300° C. or more, 350° C. or more, 400° C. or more, 450° C. or more, or 500° C. or more from the viewpoint of more easily achieving charge / discharge characteristics equivalent to those of a battery produced using an unused positive electrode active material, and may be 1000° C. or less, 800° C. or less, 700° C. or less, 600° C. or less, or 500° C. or less from the same viewpoint.
[0125] The atmosphere for the heat treatment is not limited, but an oxygen-containing atmosphere such as air is preferable. The holding time for the heat treatment can be 1 minute to 24 hours. In particular, it is preferable to heat at a temperature higher than that in step (2) for 0.1 to 5 hours.
[0126] The recycled positive electrode active material obtained from the battery mixture by using the method for producing the recycled positive electrode active material of the present invention can be used in the same way as an unused positive electrode active material. The method for producing a positive electrode and a battery using the recycled positive electrode active material is the same as the method for producing a positive electrode and a battery using an unused positive electrode active material, and is well known.
[0127] The charge and discharge characteristics of the battery manufactured using the positive electrode active material obtained by the manufacturing method of the recycled positive electrode active material according to one embodiment of the present invention are comparable to those of the battery manufactured using the unused positive electrode active material. Specifically, for example, the recycle degree of the initial charge capacity (initial charge capacity of the battery manufactured using the recycled positive electrode active material / initial charge capacity of the battery manufactured using the unused positive electrode active material) when constant current charging is performed at a current value of 0.2C to a maximum charge voltage of 4.3V in an environment of 25°C of the battery manufactured using the positive electrode active material obtained by the manufacturing method of the recycled positive electrode active material according to one embodiment is 0.98 to 1.02, which is equivalent to the initial charge capacity of the battery manufactured using the unused positive electrode active material. Furthermore, when a battery manufactured using the positive electrode active material obtained by the manufacturing method for a recycled positive electrode active material according to one embodiment is subjected to constant current discharge at a current value of 0.2 C to a minimum discharge voltage of 2.5 V in an environment of 25° C., the recycling degree of the initial discharge capacity (initial discharge capacity of the battery manufactured using the recycled positive electrode active material / initial discharge capacity of the battery manufactured using an unused positive electrode active material) is 0.9 to 1.1, which is equivalent to the initial charge capacity of a battery manufactured using an unused positive electrode active material.
[0128] In this specification, the positive electrode active material that has undergone steps (1) to (3) is referred to as a recycled positive electrode active material. The recycled positive electrode active material that has undergone steps (1) to (3) can be suitably used for manufacturing a positive electrode or the like. The manufacturing method of the recycled positive electrode active material may include additional steps before and after steps (1) to (3). In this specification, the positive electrode active material that has undergone additional steps other than steps (1) to (3) is also referred to as a recycled positive electrode active material. Examples of the additional steps other than steps (1) to (3) are a pre-step (A) and a pre-step (B) that are performed before step (1). EXAMPLES
[0129] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0130] <Production of positive electrodes> The positive electrode described below was prepared by the following procedure. A mixture was obtained by mixing 90 parts by mass of a positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by mass of a binder (manufactured by Kureha Corporation, product number: PVdF#1100), and 7 parts by mass of carbon black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. The mixture was kneaded in an agate mortar to prepare a positive electrode mixture paste. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 52% by mass.
[0131] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 10.0 ± 0.2 mg / cm2. 2 The positive electrode composite paste was applied so that the positive electrode was formed as follows: After that, it was vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of this positive electrode was 1.65 cm 2 It was.
[0132] <Battery manufacturing> The coin-type battery described below was produced by the following procedure. The above-mentioned positive electrode, electrolyte, separator, and negative electrode were combined to produce a coin-type battery (non-aqueous electrolyte secondary battery). The battery was assembled in a glove box with an argon atmosphere. As the electrolyte, a solution in which LiPF6 was dissolved at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was used. As the separator, a laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used. Metallic lithium was used as the negative electrode.
[0133] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.05 Ni 0.34 Co 0.33 Mn 0.33 A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. The rated capacity of this positive electrode active material was 160mAh / g, and the 1C current was 160mA / g. The coin-type battery was prepared using this positive electrode active material (unused positive electrode active material), and the initial charge / discharge was performed under the following conditions while maintaining the temperature at 25°C. The initial charge capacity was 178.1mAh / g, and the initial discharge capacity was 163.1mAh / g. (conditions) Maximum charging voltage: 4.3V, charging current: 0.2C, constant current constant voltage charging Minimum discharge voltage: 2.5V, discharge current: 0.2C, constant current discharge
[0134] Example 1 The electrode mixture was mechanically scraped off from the cathode of the process waste material generated during the preparation of the above cathode, and the electrode mixture was peeled off from the current collector. 30 g of the electrode mixture removed from the cathode was mixed with 10 mol of Li2CO3 per 100 mol of the cathode active material and 10 mol of Na2SO4 per 100 mol of the cathode active material as activation treatment agents to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 510°C.
[0135] 30 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300° C. / h, a heating temperature of 450° C. (lower than the melting start temperature of the activation treatment agent), and a heating time of 360 minutes.
[0136] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried under reduced pressure at 100°C for 1 hour.
[0137] The dried solid component was placed in an electric furnace and heated in an air atmosphere at a heating temperature of 700°C for 60 minutes to obtain a recycled positive electrode active material after heating. The heated recycled positive electrode active material was then naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 178.5mAh / g, and the initial discharge capacity was 160.0mAh / g.
[0138] Example 2 A recycled positive electrode active material was obtained in the same manner as in Example 1, except that the temperature at which the dried solid component was heated was changed to 900°C. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 180.5mAh / g, and the initial discharge capacity was 161.1mAh / g.
[0139] Example 3 A recycled positive electrode active material was obtained in the same manner as in Example 1, except that the temperature at which the dried solid component was heated was changed to 950°C. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 180.4mAh / g, and the initial discharge capacity was 160.8mAh / g.
[0140] Example 4 A recycled positive electrode active material was obtained in the same manner as in Example 2, except that 10 mol of Na2CO3 (melting start temperature: 851°C) was used as an activation treatment agent for 100 mol of the positive electrode active material, 10 g of the electrode mixture removed from the positive electrode was mixed with the activation treatment agent to obtain a mixture before heating. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were similar to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 180.4 mAh / g, and the initial discharge capacity was 159.7 mAh / g.
[0141] Example 5 A recycled positive electrode active material was obtained in the same manner as in Example 4, except that the temperature at which the dried solid component was heated was changed to 950°C. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 180.7mAh / g, and the initial discharge capacity was 159.5mAh / g.
[0142] Example 6 A recycled positive electrode active material was obtained in the same manner as in Example 2, except that 10 mol of K2CO3 (melting start temperature: 891°C) was used as an activation treatment agent for 100 mol of the positive electrode active material, 10 g of the electrode mixture removed from the positive electrode was mixed with the activation treatment agent to obtain a mixture before heating. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were similar to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 174.0 mAh / g, and the initial discharge capacity was 157.1 mAh / g.
[0143] Example 7 A recycled positive electrode active material was obtained in the same manner as in Example 6, except that the temperature at which the dried solid component was heated was changed to 950°C. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 174.4mAh / g, and the initial discharge capacity was 157.0mAh / g.
[0144] Comparative Example 1 A recycled positive electrode active material was obtained in the same manner as in Example 1, except that the temperature at which the mixture before heating was heated was changed to 700°C (above the melting start temperature). The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 172.2mAh / g, and the initial discharge capacity was 155.9mAh / g.
[0145] Comparative Example 2 A recycled positive electrode active material was obtained in the same manner as in Example 2, except that the temperature at which the mixture before heating was heated was changed to 700°C (above the melting start temperature). The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 172.8mAh / g, and the initial discharge capacity was 155.9mAh / g.
[0146] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.18 Ni 0.34 Co 0.33 Mn 0.33 A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. The rated capacity of this positive electrode active material was 160mAh / g, and the 1C current was 160mA / g. The coin-type battery was prepared using this positive electrode active material (unused positive electrode active material), and the initial charge / discharge was performed under the following conditions while maintaining the temperature at 25°C. The initial charge capacity was 168.9mAh / g, and the initial discharge capacity was 156.0mAh / g. (conditions) Maximum charging voltage: 4.3V, charging current: 0.2C, constant current constant voltage charging Minimum discharge voltage: 2.5V, discharge current: 0.2C, constant current discharge
[0147] Example 8 The electrode mixture was mechanically scraped off from the positive electrode of the process waste material generated when the above positive electrode was produced, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was mixed with 10 mol of Li2CO3 per 100 mol of the positive electrode active material and 10 mol of Na2SO4 per 100 mol of the positive electrode active material as activation treatment agents to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 510°C.
[0148] 40 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300°C / h, a heating temperature of 500°C (below the melting temperature of the activation treatment agent), and a heating time of 60 minutes. The air flow rate was 0.5 L / min, and the gas-powder ratio was 5.8 m 3 / kg.
[0149] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried under reduced pressure at 100°C for 1 hour.
[0150] The dried solid component was placed in an electric furnace and heated in an air atmosphere at a heating temperature of 900°C for 360 minutes to obtain a recycled positive electrode active material after heating. The heated recycled positive electrode active material was then naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 171.9mAh / g, and the initial discharge capacity was 153.0mAh / g.
[0151] Example 9 The air flow rate for heating the mixture before heating was 1 L / min, and the gas-powder ratio was 11.5 m 3 A recycled positive electrode active material was obtained in the same manner as in Example 8, except that the amount of the positive electrode active material was changed to 1.0 / kg. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of the unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 170.2mAh / g, and the initial discharge capacity was 151.2mAh / g.
[0152] Comparative Example 3 The amount of the mixture before heating was 20 g, the temperature at which the mixture before heating was heated was 700°C, the heating time was 360 min, the air flow rate was 0.85 L / min, and the gas-powder ratio was 28.7 m3 A recycled positive electrode active material was obtained in the same manner as in Example 8, except that the amount of the positive electrode active material was changed to 1.0 / kg. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining at 25°C. The initial charge capacity was 167.6mAh / g, and the initial discharge capacity was 138.9mAh / g.
[0153] Comparative Example 4 A recycled positive electrode active material was obtained in the same manner as in Example 8, except that the temperature at which the dried solid component was heated was changed to 950°C. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and the initial charge and discharge were performed under the above conditions while maintaining the temperature at 25°C. The initial charge capacity was 170.1mAh / g, and the initial discharge capacity was 135.7mAh / g.
[0154] Tables 1 and 2 show the heating temperature of the mixture before heating (T1), the heating temperature of the solid component after drying (T2), the ratio of the heating temperature of the solid component after drying to the heating temperature of the mixture before heating (T2 / T1), the difference between the heating temperature of the mixture before heating and the heating temperature of the solid component after drying (T2-T1), the measured initial charge capacity and recycling degree, and the measured initial discharge capacity and recycling degree for each Example and Comparative Example, respectively.
[0155] [Table 1]
[0156] [Table 2]
Claims
1. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture to a temperature lower than the melting start temperature of the activation treatment agent to obtain a heated mixture. (3) A step of recovering the heated positive electrode active material from the heated mixture.
2. The method according to claim 1 , wherein in the step (3), the mixture after heating is heated at a temperature higher than that in the step (2), and the heated positive electrode active material is recovered.
3. The method of claim 1 , wherein the positive electrode active material comprises a lithium compound.
4. The manufacturing method according to claim 1 , wherein the positive electrode active material comprises a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
5. The method according to claim 1 , wherein the activation treatment agent comprises at least one compound selected from the group consisting of potassium compounds and sodium compounds.
Citation Information
Patent Citations
Method for recovering active material from discarded battery material
JP2012186150A
JPP7394267B
Method for treating waste battery
WO2021060873A1
Method for producing electrode active material, method for producing secondary battery, and secondary battery
WO2024048571A1